Regulatory Effect of PDGF/PDGFR on Hematopoiesis - Liu, Yong; Huang, Junbin; Li, Lindi; Duan, Yifei; Chong, Beng H.; Li, Liang; Yang, Mo (Seminars in Thrombosis and Hemostasis, 2024)
Platelet-derived growth factor (PDGF) is a critical cytokine with substantial regulatory effects on hematopoiesis. Recent research highlights the essential role of PDGF in the modulation of hematopoietic stem/progenitor cells (HSPCs), megakaryocytes/platelets, and thrombopoietin (TPO) synthesis within the bone marrow microenvironment. PDGF directly stimulates the proliferation and differentiation of HSPCs while also inhibiting apoptosis. In addition, PDGF indirectly enhances the production of other growth factors, including granulocyte–macrophage colony-stimulating factors. Further, PDGF regulates TPO production and influences the bone marrow milieu, thus impacting hematopoiesis and platelet formation. Mechanistically, PDGF binds to its receptor, PDGF receptor (PDGFR), thus activating the PDGF/PDGFR signaling pathway. This pathway subsequently activates phosphoinositide 3-kinase/protein kinase B, leading to the activation of downstream cytokines, including c-Fos and NF-E2, while inhibiting caspase-3 activation. Collectively, these actions have prodifferentiation and antiapoptotic effects on megakaryocytes, thereby regulating platelet production. This review provides a comprehensive analysis of the regulatory role of the PDGF/PDGFR axis in hematopoiesis, with a particular focus on platelet production, by summarizing all studies on PDGF/PDGFR from our group and globally.
Keywords: platelet-derived growth factor; platelet-derived growth factor receptor; hematopoietic stem/progenitor cells; megakaryocytes; platelets